Navigation in the Arctic. How can simulator training be used for assessment and reduction of risk? - Røds, Johan-Fredrik (UiT The Arctic University of Norway, 2018)
Over the recent years, the ship traffic in the polar areas has increased. There is reason to believe that this traffic, and especially the cruise traffic, will increase further as the ice retracts towards the poles. There is also reason to believe that with the continued focus and exposure of the Polar Region, the cruise tourism to the region will grow.The increased presence in the polar areas will create positive repercussions for several actors, both on sea and land. There will however also be negative consequences associated with the growing presence in the polar areas. Vessels will be operating with long distance to other vessels and land infrastructures. These vessels will also be operating in climate and conditions that will put extra pressure on both vessel and crew. These challenges need to be solved in order for the ship industry to operate safely in the Polar Region. The thesis is focused on navigation in the Arctic, and especially how the use of simulator exercises can be used for assessment and reduction of risk. The first part of the thesis is related to study of literature as a method for collecting theory and background information for the thesis. The theoretical basis is then used for performing a preliminary hazard analysis for navigation in the Arctic. Based on the results from the analysis it is described how simulator training can be used as a risk-reducing measure for operation in the Arctic. It is also described for which hazards simulator training is an effective measure and for which hazards other techniques will be more useful.